Implementation of e-Facturing Applications for Taxable Entrepreneurs (PKP) in Running their Tax Obligations at PT. Intisubur Kimindo Raya Medan - Irma Maharani; Porkas S. Lubis; Widia Wardani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the application of the e-faktur application for Taxable Entrepreneurs (PKP) in carrying out their tax obligations at PT. Intisubur Kimindo Raya Medan. To find out whether the implementation of the e-faktur application can increase the compliance of Taxable Entrepreneurs (PKP) in carrying out their tax obligations. To analyze and find out what are the obstacles to implementing e-faktur applications in carrying out tax obligations. This research method uses a descriptive qualitative approach. Data collection techniques with documentation and interviews with related parties. Based on this research, the implementation of the e-faktur application has not been fully able to increase the compliance of Taxable Entrepreneurs (PKP) in carrying out their tax obligations. This is due to the lack of understanding and knowledge of Taxable Entrepreneurs (PKP) regarding e-faktur applications and do not understand how to operate e-faktur applications. In the e-invoice application there are also problems such as failing to upload tax invoices/errors, late updating of the e-invoice application to the latest version and internet connection disruptions which hinder the use of the e-invoice application. At PT. Intisubur Kimindo Raya Medan, e-Faktur began to be implemented in July 2016. When e-Faktur was implemented, not all taxable entrepreneurs (PKP) used e-Faktur. In other words, a taxable entrepreneur (PKP) with an active status but has not used or registered an e-Faktur, which means that the taxpayer cannot be categorized as a compliant taxpayer. Taxpayers are divided into two categories, some are compliant and some are not. Taxable Entrepreneurs (PKP) who have not used e-Faktur means that it is included in the criteria for non-compliant taxpayers. Compliant taxpayers are those who have carried out their tax obligations such as submitting or filling out their SPT. So, for taxable entrepreneurs (PKP) who have not used e-faktur, they may not know or do not understand their tax obligations.